Fishermen as a Suitable Population for HIV Intervention Trials - Zachary A. Kwena; Craig R. Cohen; Norton M. Sang; Musa O. Ng'ayo; Jeremiah H. Ochieng; Elizabeth A. Bukusi (AIDS Research and Treatment)
Background. Suitable populations to sustain continued evaluation of HIV and sexually transmitted infection (STI) prevention interventions are required. We sought to determine whether fishermen are a suitable population for HIV intervention trials. Methods. In a cross-sectional descriptive survey, we selected 250 fishermen from proportional to size sampled boats. We collected socioeconomic and behavioral information, and specimens for HIV, herpes simplex virus (HSV-2), syphilis, gonorrhea, chlamydia and human papillomavirus (HPV) tests from consenting participants. Results. One third of the fishermen had concurrent sexual partnerships and two thirds were involved in transactional sex. About 70% were involved in extramarital sex with only one quarter using condoms in their three most recent sexual encounters. HIV prevalence was 26% and HSV-2 and HPV was 57%. Over 98% were willing to participate in a future HIV prevention clinical trial. Conclusion. Fishermen are a high-risk group for HIV/STI infections that may be suitable for HIV prevention trials. A cohort study would be useful to measure the incidence of HIV/STIs to ultimately determine the feasibility of enrolling this population in an HIV/STI prevention clinical trial.